A study on the modern transformation and design of Jieshou painted pottery patterns from the perspective of shape grammar / Li Bo Hao and Musnin Misdih - Li, Bo Hao; Misdih, Musnin (Universiti Teknologi MARA, Kedah, 2025)
Jieshou painted pottery is a form of folk art from Jieshou City in China. Despite being listed among China's first batch of cultural heritage sites, its inheritance situation is less than optimistic due to a lack of effective promotion. This study explores the application of Jieshou painted pottery patterns in modern cultural and creative products to safeguard the preservation and development of Jieshou pottery culture and to activate pathways for its inheritance. The research combines Shape Grammar (SG) theory with literature analysis, utilizing computer-aided design to delve deeply into the patterns of Jieshou painted pottery. By creating new derivative patterns through the morphological inference of SG and applying them to cultural and creative designs, these derivative patterns enrich the traditional visual expression of Jieshou pottery patterns and broaden avenues for cultural dissemination and promotion. It also substantially advances effective communication and dynamic inheritance of our country's traditional cultural resources within a contemporary context.